Animal and human health: tackling uncertainty through participatory modelling and simulation - Duboz, Raphaël; Binot, Aurélie (Perspective, 2017)
<span style="font-size: 10pt; font-family: Arial; font-style: normal;" data-sheets-value=""1":2,"2":"Zoonoses – infectious diseases communicable between animals and humans –, drug resistance and environmental pollution are now causing serious health problems worldwide. These problems are closely tied to global environmental and socio-economic changes and to the transformation of production systems at the territorial level. In this context, health management is becoming a complex issue: it needs to be addressed in close collaboration with the public veterinary health, agriculture and environment sectors. New uncertainties are emerging, and nonconventional actors are entering the scene alongside the decision-makers traditionally responsible for public health. The participatory modelling and simulation approach incorporates the diverse knowledge of all of these actors. It reveals uncertainties and teaches participants how to manage them, to make decisions and to share responsibility. It constitutes a practical solution to ensure health issues are better integrated into territorial planning policies."" data-sheets-userformat=""2":587,"3":[null,0],"4":[null,2,16777215],"6":"1":["1":2,"2":0,"5":[null,2,0],"1":0,"2":0,"3":3,"1":1,"2":0,"4":1],"9":0,"12":0">Version française de l'article <span style="font-size: 10pt; font-family: Arial; font-style: normal;" data-sheets-value=""1":2,"2":"Zoonoses – infectious diseases communicable between animals and humans –, drug resistance and environmental pollution are now causing serious health problems worldwide. These problems are closely tied to global environmental and socio-economic changes and to the transformation of production systems at the territorial level. In this context, health management is becoming a complex issue: it needs to be addressed in close collaboration with the public veterinary health, agriculture and environment sectors. New uncertainties are emerging, and nonconventional actors are entering the scene alongside the decision-makers traditionally responsible for public health. The participatory modelling and simulation approach incorporates the diverse knowledge of all of these actors. It reveals uncertainties and teaches participants how to manage them, to make decisions and to share responsibility. It constitutes a practical solution to ensure health issues are better integrated into territorial planning policies."" data-sheets-userformat=""2":587,"3":[null,0],"4":[null,2,16777215],"6":"1":["1":2,"2":0,"5":[null,2,0],"1":0,"2":0,"3":3,"1":1,"2":0,"4":1],"9":0,"12":0">Zoonoses – infectious diseases communicable between animals and humans –, drug resistance and environmental pollution are now causing serious health problems worldwide. These problems are closely tied to global environmental and socio-economic changes and to the transformation of production systems at the territorial level. In this context, health management is becoming a complex issue: it needs to be addressed in close collaboration with the public veterinary health, agriculture and environment sectors. New uncertainties are emerging, and nonconventional actors are entering the scene alongside the decision-makers traditionally responsible for public health. The participatory modelling and simulation approach incorporates the diverse knowledge of all of these actors. It reveals uncertainties and teaches participants how to manage them, to make decisions and to share responsibility. It constitutes a practical solution to ensure health issues are better integrated into territorial planning policies.